Monsoon variability trends and strategies to get through its vagaries in rice-based systems in eastern India - Panneerselvam, P.; Singh, Sudhanshu (CAB International, 2019)
The trend of increasing monsoon variability in eastern India has led to increased risk of growing crops during the monsoon period. The rainfall pattern has become more erratic due to the shrinking of monsoon period 60-70 days from the normal 120 days, leading to drought and unusual frequent torrential rainfall exceeding 200-250 mm/day, causing floods during the past few decades. The duration and magnitude of drought and the number of dry spells also have increased. These stresses not only affect the yield of rice but also reduce the area and production of succeeding crops, resulting in low system productivity. Rice is the major crop in monsoon season in eastern India. Hence, technological or management options to cope with monsoon variability are discussed based on the available literature and results from the experiments conducted in eastern India, particularly in Odisha. Direct seeded rice (DSR) is an apt option for delayed onset of the monsoon that enables better use of early rains. In this regard, DSR helps reduce the risk of-of late-season drought by avoiding the stress period. Thus, DSR allows farmers to undertake early sowing of the subsequent crops, leading to higher system productivity. The performance of short-duration drought- and flood-tolerant rice varieties in stress-prone areas are reviewed and discussed here. Rice nursery enterprise in private- as well as community-sector has been proved as an effective strategy to ensure timely availability of healthy seedlings. However, the scale of these technologies/management options in eastern India is facing a tough challenge due to weed infestation, lack of availability of tolerant anaerobic and stagnant flood varieties, and appropriate machinery, in addition to socio-economic constraints to access the technologies.